A Radiological Study on Cervical Rib and Associated Chest Wall Anomalies (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To reveal the association of cervical rib with chest wall anomalies.Methods: Observational study conducted at the private radiology clinics Rawalpindi & Islamabad from January 2015 to December 2017, which included Patients coming for X-RAY chest. The patients were selected through convenience sampling. Radiographs were discussed with a consultant radiologist to diagnose the cervical rib and associated anomalies of sternum and rib cage. The age groups were from one to thirty-five years.Results: The study comprises one hundred and fifty patients. Fifty-eight ere female and ninety-two were male patients. The ages of patients were between 10-35 years. The cervical rib was detected in 8.69% male patients and 5.17% female patients.  Bifid ribs, Diaphyseal aclasis, fused ribs and Rachitic rosary was found in 1.008% of the cases. No sternal anomaly was detected.Conclusion: Association of Rib anomalies with cervical rib is more common as compared to sternal and vertebral anomalies.